CATHODIC PROTECTION IN ONSHORE PIPE NETWORKS GAS PAGARDEWA RECEIVING STATION - Arwati, I Gusti Ayu; N, Euis; Sirait, Dedi (World Chemical Engineering Journal, 2019)
The use of pipelines is one element that plays an important role as a production chain The pipeline network is used as the main component to distribute gas from the producer to the shipper and then distributed to industrial and household customers. In accordance with the regulations of the Ministry of Mines and Energy No. 300. K / 38 / M.PE / 1997 concerning the Occupational Safety of Petroleum and Gas Pipeline Pipes that the gas and main pipe transmission pipes held on land must be planted with a depth of at least 1 (one) meter above ground level.  However, the placement of steel pipes in the ground can cause pipe material to be threatened by corrosion due to interaction with the environment. This happens in the Pipeline Line of the Gas Pagardewa receiving station. To prevent corrosion from continuing on the pipeline, a precautionary step is needed where one of them is by applying the cathodic protection method. At Pagardewa Gas Receiver Station, which has the role of distributing gas to PLN's power plan in South Sumatra by using a 4875 m pipeline that is embedded in the ground so it needs to be designed for a cathodic protection system to be corrosion resistant. The purpose of this study is to design a cathodic protection system that uses sacrificial anodes so that the analysis can be obtained to be applied in the field.